Linguistic-Ethnic Barrier In Translation - Jalilova Lola Jalilovna; Hamidova Xonzodabegim Niyoziyevna (Zien Journals, 2024)
This article examines the specifics of the lingua-ethnic barrier in translation and ways to overcome it that is of particular importance at the present stage of the development of lingua cultural studies. In this article, we will identify and substantiate the main factors of lingua-ethnic barriers, and look for ways to overcome them.
Keywords: lingua-ethnic barrier; translation